Magic power of self image psychology - "Maltz, Maxwell" (Mumbai, 2003)
Are you depressed? Has your selfesteem hit an all time low? Do you wish to be calm, cool and collected at all times and turn your life into a blazing success story. Dr. Maltz$1 (Bs foolproof formula guarantees to change your life forever. He proves that selfesteem influences every thought and action and undertakes to build up your selfesteem through seven easy mental exercises that will cast out all your fears, anxieties and resentments, replacing them with pleasure and selfconfidence. So invest your time and energy wisely. Let mind power magic work on you and watch it transform you totally.s
Keywords: Psychology